Analisis Penerimaan Penggunaan Aplikasi WeTV di Pulau Jawa Menggunakan Metode Technology Acceptance Model (TAM) - Hikmah Safitri; Diovianto Putra Rakhmadani; Shintia Dwi Alika (STMIK Budi Darma, 2022)
Every human being always needs what is called entertainment andwith the help of the internet entertainment facilities are not only obtained in the real world but can also be obtained in the virtual world. There are many entertainment facilities to watch online videos in Indonesia, one of which is by using the WeTV application. WeTV is an application owned by Tencent Video that conducts ekspansi in Indonesia, WeTV was present in 2019 as an application that presents a variety of interesting online video content from several countries that can be accessed and can be enjoyed by the Indonesian people because it is equipped with a translator Indonesian. The purpose of this study is tofind out the factors that influence the acceptance of WeTV applications using the Technology Acceptance Model (TAM) method with research variables Preceived Usefulness, Perceived Ease of Use, Attitude Toward Use, Intentation To Use and Actual Usage. The distribution of questionnaires was carried out online with a minimum sample of the number of respondents determined by the slovin formula and and teknik sampling using simple random sampling. This study used PLS-SEM data analysis with SmartPLS tools. The results of this study found that the factors that most influenced the acceptance of WeTV applications in Pulau Jawa were the variable Perceived Ease of Use (ease) to Perceived Usefulness (usability).